The Influence of Bonuses on Employee Performance in PT. XWZ - Tutik Rahayu; Darka Darka; Aliy Rasyid; Hari Hariadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to find out how much influence bonuses have on employee performance at PT. Xwz. The sub-variables studied in giving bonuses are performance, length of service, seniority, fairness and suitability. Meanwhile, employee performance is quality of work, quantity of work, punctuality, effectiveness and independence. The method used in this research is a descriptive research method with a quantitative approach aimed at 60 respondents where the entire population was used as a sample. The data sources in this research are primary and secondary data. To test the questionnaire instrument or questionnaire, validity and reliability tests are used. Meanwhile, to analyze the data obtained, a simple linear regression test was used with the results of giving bonuses having a positive effect, the correlation coefficient test with the results of giving bonuses had a strong relationship to employee performance, the coefficient of determination with the results of giving bonuses had an influence on employee performance while the rest was influenced by factors. other than the object under study, and the t test can be concluded that giving bonuses has a positive and significant effect on employee performance.